A Chironomidae-based reconstruction of the Saalian-Eemian transition (mis 6a–mis 5e) in a palaeolake from the “Parchliny 2016” profile, central Poland - Płóciennik , Mateusz; Łukawska , Sylwia; Janowska , Ewa; Krzyszkowski , Dariusz; Wieczorek , Dariusz; Wachecka-Kotkowska , Lucyna (Acta Geographica Lodziensia, 2024)
Abstract. In the end of Saalian Glaciation (Wartanian Stadial, MIS 6a) there formed many glacial depressions, melt-out kettle holes and subglacial channels in central Poland’s ice-marginal zone. In these landforms, there developed a lakeland that existed to the Early Weichselian (5d-a). Following excavation in 2016 on the eastern wall of the Szczerców field, lacustrine deposits were recognised in the Parchliny 2016 profile. A previous multi-proxy study of the Parchliny 2016 profile concerning a reconstruction of the palaeolake included analyses of pollen, plant macrofossils, wood macrofossils, diatoms, cladocerans, ostracods and molluscs. The present work presents the Chironomidae analysis for the above-mentioned section. The collected subfossils could be identified from the keys presenting modern Palaearctic fauna. The Chironomidae indicate a temperate climate in the region and favourable, meso/eutrophic conditions in the palaeolake during the Late Saalian (MIS 6a). The changes in subfossil numbers reveal that the Zeifen interstadial fells at 24.38–24.23 m core depth and the subsequent Kattegat stadial at 24.18– –23.83 m, but head capsule count is too low for quantitative temperature estimations. From the Eemian (MIS 5e) transition, they decline in the sediment and are represented only by two head capsules at the 23.33 m core depth below the ground surface. The increase in summer temperature, trophic status and stratification of the lake may have caused an oxygen depletion that eliminated sensitive taxa. However, no species are observed that are resistant to eutrophication and anoxia replacing sensitive ones in the assemblages. Sediment desiccation and compaction may have caused the decomposition of Chironomidae subfossils in the deposits from the Eemian interglacial, so their apparent decline in the ecosystem may be misleading.